Effect of dopamine on TGF-β2 secretion by human retinal pigment epithelial cells and the underlying mechanism - Jing Fan; Qiujin Zhang; Liu Zheng; Binbin Yang; He Jin; Tingyu Meng; Zhixiang Ding (PLoS ONE, 2025)
Background Dopamine is known to play a role in the development of myopia. In this study, we investigated the effect of dopamine (DA) on the secretion of transforming growth factor-β2 (TGF-β2) in human retinal pigment epithelial (RPE) cells. Additionally, we examined the effects of SCH23390 (D1 receptor antagonist) and sulpiride (D2 receptor antagonist) on TGF-β2 levels in ARPE-19 cells to elucidate the underlying mechanism of DA in myopia development. Methods Human RPE cells were cultured with or without different concentrations of DA, SCH23390, or sulpiride. Cell proliferation was examined using the CCK-8 assay. Cell migration was assessed by performing a cell scratch (wound healing) assay. The expression of TGF-β2 was evaluated at the mRNA and protein levels by real-time PCR and western blotting, respectively. Furthermore, the secretion of TGF-β2 into the ARPE-19 cell supernatant was quantified using ELISA. Results Treatment with 20 μg/mL of DA significantly increased ( P < 0.05) the mRNA and protein expression levels of DRD1, DRD2, YAP, and TEAD and decreased TGF-β2 levels compared with that in control group. However, treatment with 24 μg/mL of SCH23390 for 24 h significantly decreased ( P < 0.05) DRD1 and TGF-β2 mRNA expression and increased DRD2 , YAP , and TEAD mRNA expression in ARPE-19 cells compared with that in the control group. Additionally, the protein expression levels of TGF-β2, YAP, TEAD, and SMAD7 were consistent with the mRNA levels. Notably, treatment with sulpiride (14 μg/mL) increased ( P < 0.05) DRD1 and TGF-β2 expression and decreased DRD2 , YAP , and TEAD expression in the cells at both the mRNA and protein levels compared with that in the control group. Conclusions Our findings suggest that dopamine suppresses TGF-β2 secretion in human retinal pigment epithelial cells primarily through activation of D2 receptors, which appears to involve the YAP-TGF-β-Smad signaling pathway. This regulatory mechanism may contribute to the control of scleral remodeling and thus influence the development of myopia.